ANALYSIS OF FEATURES OF INNOVATION PROCESSES OF MODER RUSSIA - Aleksey M. Karmanov (Статистика и экономика, 2016)
Necessity for modernization of Russian economy and its innovation development is undoubted today. Nevertheless, there are different methods of achievement these objectives. In this regard, the comprehensive analysis of features of innovation processes of modern Russia is of great importance.